'Look, I have my ears open': Resilience and early school experiences among children in an economically deprived suburban area in Ireland. (April 2016) - Tatlow-Golden, Mimi; O'Farrelly, Christine; Booth, Ailbhe; O'Rourke, Claire; Doyle, Orla
Children from economically disadvantaged communities frequently lack the socio-emotional, cognitive and behavioural skills needed for successful early school adjustment. Assessments of early school experience often rely on parent and teacher perspectives, yet children's views are essential to design effective, resilience-promoting school ecologies. This mixed methods study explored children's appraisals of potential stressors in the first school year with 25 children from a disadvantaged suburban community in Ireland. School scenarios were presented pictorially (Pictorial Measure of School Stress and Wellbeing, or PMSSW), to elicit children's perspectives on social ecological factors that enable or constrain resilience. Salient positive factors included resource provision, such as food, toys and books; school activities and routines, including play; and relationships with teachers. Negative factors included bullying; difficulties engaging with peers; and using the toilet. Drawing on these factors, we indicate how school psychologists can develop resilience-fostering educational environments for children in vulnerable communities.